(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
A model of examining the tourist risk was presented in the article. It is assumed that opinions of hotels are correlated, therefore the choice of the consumer depends on the collection of hotels with the maximum expected value of the consumer’s opinion and the minimal risk. Some hotel is taken out from the optimal set with the highest probability. The model is solved by the method of square programming with using the program Matcad. The theoretical model is used for the study of choice of consumers in hotels from the region of Kołobrzeg in 2006-2009. The model allows the customer to choose effectively the hotel with high averages and minimal risk. The idea of constant monitoring of tourist data and presenting the information to the consumer is also sug-gested in the article. The introduced model could be applied for the examination of different economic phenomena, based on historical data.